Sorption of Water Vapor in Poly(L-Lactic Acid): A Time-Resolved FTIR Spectroscopy Investigation - Pannico, Marianna; La Manna, Pietro (Frontiers in Chemistry, 2019)
In this contribution the sorption of water vapor in Poly(L-lactic acid) (PLLA) was studied by time-resolved FTIR spectroscopy. The collected FTIR data were analyzed by complementary approaches such as difference spectroscopy, two-dimensional correlation spectroscopy (2D-COS), and least-squares curve-fitting analysis which provided information about the overall diffusivity, the nature of the molecular interactions among the polymer and the penetrant and the dynamics of the various molecular species. The diffusion coefficient were evaluated as a function of vapor activity and were found in good agreement with previously reported values. The system showed a Fickian behavior with diffusivity increasing with penetrant concentration. Two distinct water species (first-shell and second-shell layers) were detected and quantified by coupling FTIR and gravimetric measurements.